2021
DOI: 10.3389/fmicb.2021.616045
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalis Readily Adapts Membrane Phospholipid Composition to Environmental and Genetic Perturbation

Abstract: The bacterial lipid membrane, consisting both of fatty acid (acyl) tails and polar head groups, responds to changing conditions through alteration of either the acyl tails and/or head groups. This plasticity is critical for cell survival as it allows maintenance of both the protective nature of the membrane as well as functioning membrane protein complexes. Bacteria that live in fatty-acid rich environments, such as those found in the human host, can exploit host fatty acids to synthesize their own membranes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 58 publications
2
22
1
Order By: Relevance
“…Enterococcus faecalis is a mammalian gut microbiota enriched in fatty acid-rich bile ( 45 ). Enterococcus faecalis , as a conditional pathogenic microorganism, changes into a pathogenic state when intestinal ecology is dysregulated, resulting in extensive infection ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Enterococcus faecalis is a mammalian gut microbiota enriched in fatty acid-rich bile ( 45 ). Enterococcus faecalis , as a conditional pathogenic microorganism, changes into a pathogenic state when intestinal ecology is dysregulated, resulting in extensive infection ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to peptidoglycan accumulation, serum-induced daptomycin tolerance in S. aureus occurs via an increase in cardiolipin abundance in the membrane. Therefore, we examined serum-induced daptomycin tolerance in E. faecalis mutant strains defective for one or both of the cardiolipin synthases (Δ cls1 , Δ cls2 ) and/or one of the two lysylphosphatidylglycerol synthases present in E. faecalis (Δ mprF2 ) [39].…”
Section: Resultsmentioning
confidence: 99%
“…DAP possesses a cyclic peptide core linked to a fatty acyl chain and requires calcium to adopt an amphipathic conformation that facilitates oligomerization and insertion into the bacterial membrane. In addition, complex formation with calcium masks the lipopeptides’s negative charge and increases its affinity for the membrane lipid PG, the major constituent of Gram-positive membranes (typically comprising 50%–65% of the total APL content in S. aureus and E. faecalis ( Müller et al, 2016 ; DeMars et al, 2020 ; Kotsogianni et al, 2021 ; Woodall et al, 2021 ). Recent structural analysis of Ca 2+ -DAP in lipid bilayers containing PG shows that DAP forms tetramers within the outer leaflet ( Beriashvili et al, 2020 ).…”
Section: Mechanism Of Action Of Daptomycinmentioning
confidence: 99%
“…Interestingly, a different analysis of membrane lipids of the DAP-R E. faecalis strain performed by 2D-TLC during exponential growth showed a significant increase in PG, a reduction in CL, and no differences in lysyl-PG as compared to S613, while levels of GP-DGDAG were not reported ( Khan et al, 2019 ). Thus, lipid alterations other than a decrease in membrane PG are likely to also contribute to DAP-R. A recent study showed that the absence of CL in E. faecalis OG1RF, achieved by deletion of both CL synthases, increased sensitivity to DAP and other cell damaging agents such as SDS, while the absence of lysyl-PG, resulting from deletion of mprF2 , did not change sensitivity to DAP but rendered the mutant more resistant to SDS ( Woodall et al, 2021 ). The triple mutant, which lacked CL and lysyl-PG, restored membrane tolerance to DAP and SDS to the level of parental strain OG1RF.…”
Section: Alterations Of Membrane Lipids Associated With Changes In Da...mentioning
confidence: 99%